2002
DOI: 10.5194/angeo-20-321-2002
|View full text |Cite
|
Sign up to set email alerts
|

Interball-tail observations of vertical plasma motions in the magnetotail

Abstract: Abstract. The Interball spacecraft configuration favors, in contrast to previous experiments, investigation of vertical ion flows (GSM V z ). We use measurements of the CORALL instrument for the statistical study of V z and V y plasma flows in the mid-tail plasma sheet. In agreement with the previous observations, the mean V y was positive on the dusk side and negative on the dawn side. When IMF was southward, the mean V z consisted of the convection flow towards the equatorial plane ∼ 7 km/s and the northward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…This nonlinear decrease is consistent with intermittent turbulence of the plasma sheet and with properties of non‐self‐similar scaling. These results are consistent with those previously reported for field fluctuations [ Weygand et al , 2005] and for flow fluctuations [ Borovsky et al , 1997, 2003; Angelopoulos et al , 1999; Petrukovich and Yermolaev , 2002]. Angelopoulos et al [1999] used two spacecraft (Geotail and Wind) to demonstrate intermittency in the plasma sheet flow.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This nonlinear decrease is consistent with intermittent turbulence of the plasma sheet and with properties of non‐self‐similar scaling. These results are consistent with those previously reported for field fluctuations [ Weygand et al , 2005] and for flow fluctuations [ Borovsky et al , 1997, 2003; Angelopoulos et al , 1999; Petrukovich and Yermolaev , 2002]. Angelopoulos et al [1999] used two spacecraft (Geotail and Wind) to demonstrate intermittency in the plasma sheet flow.…”
Section: Discussionsupporting
confidence: 90%
“…Turbulence has been identified in the magnetospheric plasma sheet as well as in the solar wind. For plasma sheet studies different methods that have been used that include statistical examinations of PDFs of flow and magnetic field and the fluctuations of these quantities [ Borovsky et al , 1997; Angelopoulos et al , 1999; Petrukovich and Yermolaev , 2002; Weygand et al , 2005]. Most of these studies found non‐Gaussian PDFs of flow and magnetic field fluctuations from which they concluded that the plasma was turbulent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 6, the deviation of the histogram is much larger than the averaged velocity for all conditions. This is the same for plasma sheet observations [ Angelopoulos et al , 1993; Petrukovich and Yermolaev , 2002]. However, while the high‐beta plasma in the plasma sheet may have a turbulent nature [ Angelopoulos et al , 1999], the lobe convection should be much more laminar, if compared with the polar cap convection.…”
Section: Discussionmentioning
confidence: 63%
“…For some time it has been noted that the flows of the plasma sheet are irregular [e.g., Hones and Schindler , 1979; Hayakawa et al , 1982; Sergeev and Lennartsson , 1988; Angelopoulos et al , 1993; Nakamura et al , 1994; BEFT1997; Yermolaev et al , 2000; Ovchinnikov et al , 2000; Neagu et al , 2002; Petrukovich and Yermolaev , 2002]. Consistent with the turbulent flow velocities, large fluctuations in the electric field are observed by satellites in the plasma sheet [ Cattell and Mozer , 1982; Cattell et al , 1986; Pedersen et al , 1985; BEFT1997, Figure 8].…”
Section: Introductionmentioning
confidence: 98%